2021
DOI: 10.1007/s00167-021-06717-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased patellar bone tracer uptake in preoperative SPECT/CT before medial opening high tibial osteotomy correlates with inferior clinical outcome

Abstract: Purpose The purpose of this study was to investigate whether specific bone tracer uptake (BTU) patterns on preoperative SPECT/CT could predict which patients with varus alignment and medial overload would particularly benefit from medial opening-wedge high tibial osteotomy (MOWHTO). It was the hypothesis that an increased preoperative BTU relative to the reference BTU of the femur on SPECT/CT in the lateral and patellar compartments of the knee are predictive factors for inferior clinical outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This issue has been controversial, and additional preoperative assessments may be necessary to anticipate the clinical outcome [36]. However, in the authors' opinion, an accuracy of ± 1.5°, as mentioned before, seems necessary when performing varus correction osteotomies because biomechanical studies have observed a signiicant load shift beginning at 3° of varus [4,8].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This issue has been controversial, and additional preoperative assessments may be necessary to anticipate the clinical outcome [36]. However, in the authors' opinion, an accuracy of ± 1.5°, as mentioned before, seems necessary when performing varus correction osteotomies because biomechanical studies have observed a signiicant load shift beginning at 3° of varus [4,8].…”
Section: Discussionmentioning
confidence: 87%
“…The clinical relevance of overcorrection was shown in a study by Hohloch et al, who demonstrated in a comparative study of HTOs aiming for postoperative 50–55%, 55–60% and > 60% mTFA intersection significantly better results in terms of Lysholm Score and Knee Injury and Osteoarthritis Outcome Score (KOOS) for a 50–55% intersection [ 13 ]. This issue has been controversial, and additional preoperative assessments may be necessary to anticipate the clinical outcome [ 36 ]. However, in the authors’ opinion, an accuracy of ± 1.5°, as mentioned before, seems necessary when performing varus correction osteotomies because biomechanical studies have observed a significant load shift beginning at 3° of varus [ 4 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, only the cartilage status of the medial compartment was assessed in this study. Schelker et al [29] reported that increased patellar bone tracer uptake in preoperative SPECT/CT before OWHTO correlates with inferior clinical outcomes. Not only should the medial compartment be considered, but preoperative conditions, the patellofemoral joint and the lateral compartment must also be assessed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Sixth, the effect of the patellofemoral joint on the clinical outcomes was not evaluated. A recent study reported inferior post‐operative outcomes in patients with increased patellar bone tracer uptake on pre‐operative SPECT/CT [26]. BML in the patellofemoral joint might affect clinical outcomes after HTO.…”
Section: Discussionmentioning
confidence: 99%